Hs-CRP, Diabetic Status, and Adverse Events Among Patients Receiving Statin Therapy Following PCI—A Prospective Registry-Based Study - Chen X; Wang HY; Sun W; Lin Z; Qiao Z; Bian X; Yin D; Feng L; Zhu C; Song W; Wang H; Jia L; et al. (Journal of Inflammation Research)
Xinyue Chen,1– 3,* Hao-Yu Wang,1– 4,* Wanqing Sun,1– 3,* Zhangyu Lin,1– 3 Zheng Qiao,1– 3 Xiaohui Bian,1– 3 Dong Yin,1 Lei Feng,1 Chenggang Zhu,1 Weihua Song,1 Hongjian Wang,1 Lei Jia,1 Qiuting Dong,1 Kefei Dou1– 4 1Cardiometabolic Medicine Center, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 2Coronary Heart Disease Center, Department of Cardiology, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China; 3State Key Laboratory of Cardiovascular Disease, Beijing, People’s Republic of China; 4National Clinical Research Center for Cardiovascular Diseases, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Kefei Dou; Hao-Yu Wang, Cardiometabolic Medicine Center, Coronary Heart Disease Center, Department of Cardiology, Fuwai Hospital, State Key Laboratory of Cardiovascular Disease, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences and Peking Union Medical College, No.167 North Lishi Road, Xicheng District, Beijing, 100037, People’s Republic of China, Tel +86-13801032912, Fax +86-10-6831-3012, Email drdoukefei@126.com; wanghaoyu@fuwai.comPurpose: Inflammation represents a key driver of type 2 diabetes (T2DM) and is associated with major adverse cardiovascular and cerebrovascular events (MACCEs). Residual inflammatory risk, defined as persistent inflammation despite lipid-lowering therapy, differs from residual cholesterol risk, which refers to suboptimal lipid levels post-treatment. This study aims to evaluate the impact of T2DM on the relationship between residual inflammatory risk, as assessed by a simple, economical, and easily measurable biomarker—high-sensitivity C-reactive protein (hs-CRP)—and clinical outcomes in statin-treated coronary heart disease (CHD) patients with drug-eluting stent (DES) implantation.Patients and Methods: 8,628 individuals with CHD treated with statins and DES implantation at Fuwai Hospital were included. Participants were first stratified according to T2DM status, and then baseline hs-CRP levels were further divided into three groups using 1 mg/L and 2 mg/L as the cut-off points. The primary endpoint was MACCEs, defined as the composite of all-cause mortality, myocardial infarction, stroke, and target vessel revascularization.Results: After 2.4 years of median follow-up duration, 999 patients were defined as MACCEs, whose hs-CRP levels were significantly higher compared to the non-MACCEs group (p = 0.007). The cohort was stratified into T2DM (n = 3,729) and Non-T2DM (n = 4,899) groups. In full adjusted model: for the Non-T2DM group, hs-CRP ≥ 2 mg/L remained significantly associated with MACCEs [HR = 1.39, 95% CI (1.14– 1.85), p = 0.002]. In the T2DM group, no significant association was observed [HR = 1.02, 95% CI (0.73– 1.23), p = 0.453] (p for interaction= 0.040).Conclusion: Among CHD patients receiving contemporary statin therapy following DES implantation, higher hs-CRP levels appeared to be associated with future MACCEs in those without T2DM, though not in T2DM patients. Hs-CRP, an important diagnostic marker of inflammation, shows different value depending on diabetes status, revealing how diabetes and inflammation jointly influence cardiovascular outcomes and providing clinical insights for optimizing the application of inflammatory biomarkers in personalized cardiovascular risk stratification.Keywords: high-sensitivity C-reactive protein, risk of residual inflammation, coronary heart disease, statin therapy, diabetes mellitus, major adverse cardiovascular and cerebrovascular events